Leprosy and colonialism : Suriname under Dutch rule, 1750-1950 - Snelders, Stephen, 1963- (Social histories of medicine., 2017)
Leprosy and colonialism investigates the history of leprosy in Suriname within the context of Dutch colonial power and racial conflict, from the plantation economy and the age of slavery to its legacy in the modern colonial state.